2020
DOI: 10.3390/app10103533
|View full text |Cite
|
Sign up to set email alerts
|

Drying Performance and Aflatoxin Content of Paddy Rice Applying an Inflatable Solar Dryer in Burkina Faso

Abstract: The drying performance of paddy rice using an inflatable solar dryer (ISD), or also known as GrainPro® Solar Bubble Dryer™, was evaluated and compared to conventional sun drying in Burkina Faso. Drying time was around eight hours. Thermal imaging was conducted to observe temperature distribution in the ISD during drying and mixing. Shadow casting was observed in the ISD due to the round shape of the black plastic film, which reduced the temperature of the paddy rice to about 10 °C. The temperature inside the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Drying with ISD should be planned as best as possible to maximise the solar energy and prevent contamination by mycotoxins. Experiments on rice in Burkina Faso also showed that the ISD dried rice had less aflatoxins and impurities compared to conventional sun-dried rice [27]. This slight effect observed for maize in our research was not significant enough to reduce the contamination level of aflatoxins.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Drying with ISD should be planned as best as possible to maximise the solar energy and prevent contamination by mycotoxins. Experiments on rice in Burkina Faso also showed that the ISD dried rice had less aflatoxins and impurities compared to conventional sun-dried rice [27]. This slight effect observed for maize in our research was not significant enough to reduce the contamination level of aflatoxins.…”
Section: Discussioncontrasting
confidence: 66%
“…Its application in cereal drying, initially with paddy rice, was promising, but improvements were needed, such as the ability to mix the grains to achieve a homogeneous drying process [25]. The inflatable solar dryer was developed in collaboration with the International Rice Research Institute (IRRI) as an improved version, which is adapted to cereal crops in tropical regions [26,27]. Asemu et al [28] conducted experiments on the use of an inflatable solar dryer to dry maize.…”
Section: Introductionmentioning
confidence: 99%
“…Rice 1000 [71] Drying performance and Aflatoxin content of paddy rice applying an inflatable solar dryer in Burkina Faso…”
Section: Inflatable Solar Dryermentioning
confidence: 99%
“…The ISD design characteristics are: ease of transport and installation; simple operation compared to mechanical dryers; low maintenance since it is made of plastic material. Currently, the ISD has been successfully tested on paddy rice [16,17], amaranth leaves [18], mushrooms [19], and maize [20]. However, information on airflow distribution or heat and mass transfer of the ISD is still lacking.…”
Section: Introductionmentioning
confidence: 99%